Artificial light at night (ALAN) alters the physiology and biochemistry of symbiotic reef building corals - Levy, Oren; Fernandes de Barros Marangoni, Laura; I. C. Benichou, Jennifer; Rottier, Cécile; Béraud, Eric; Grover, Renaud; Ferrier-Pagès, Christine (Environmental pollution (1987), 2020)
Artificial Light at Night (ALAN), which is the alteration of natural light levels as the result of anthropogenic light sources, has been acknowledged as an important factor that alters the functioning of marine ecosystems. Using LEDs light to mimic ALAN, we studied the effect on the physiology (symbiont and chlorophyll contents, photosynthesis, respiration, pigment profile, skeletal growth, and oxidative stress responses) of two scleractinian coral species originating from the Red Sea. ALAN induced the photoinhibition of symbiont photosynthesis, as well as an overproduction of reactive oxygen species (ROS) and an increase in oxidative damage to lipids in both coral species. The extent of the deleterious effects of ALAN on the symbiotic association and coral physiology was aligned with the severity of the oxidative stress condition experienced by the corals. The coral species Sylophora pistillata, which experienced a more severe oxidative stress condition than the other species tested, Turbinaria reniformis, also showed a more pronounced bleaching (loss of symbionts and chlorophyll content), enhanced photoinhibition and decreased photosynthetic rates. Findings of the present study further our knowledge on the biochemical mechanisms underpinning the deleterious impacts of ALAN on scleractinian corals, ultimately shedding light on the emerging threat of ALAN on coral reef ecology. Further, considering that global warming and light pollution will increase in the next few decades, future studies should be taken to elucidate the potential synergetic effects of ALAN and global climate change stressors. [Display omitted] •Light pollution can disrupt the coral-dinoflagellate symbiosis.•Light pollution promotes photoinhibition and reactive oxygen species overproduction in symbiotic corals.•Coral species show different susceptibilities to light pollution.•Higher capacity to combat reactive oxygen species may turn corals more resistant to light pollution.•Light pollution can be a major additional threat to coral reefs near heavily urbanized areas. The extent of ALAN deleterious effects on symbiotic corals was driven by the severity of the oxidative stress condition experienced by each species.